AL-KHORAZMII ZIJI AND HISTORY OF ITS CREATION - Norieva , Aziza Jasur qizi (Innovative Development in Educational Activities, 2023)
This article describes the work of the great mathematician, astronomer and geographer, the father of algebra Muhammad Al-Khorazmi "Zizhi Khorazmi" and the history of its creation, and al-Khorazmi’s great contribution to the field of astronomy is recognized.